2017
DOI: 10.1098/rspb.2017.1106
|View full text |Cite
|
Sign up to set email alerts
|

Admixture mapping in a hybrid zone reveals loci associated with avian feather coloration

Abstract: These authors contributed equally to this study. Identifying the genetic bases for colour patterns has provided important insights into the control and expression of pigmentation and how these characteristics influence fitness. However, much more is known about the genetic bases for traits based on melanin pigments than for traits based on another major class of pigments, carotenoids. Here, we use natural admixture in a hybrid zone between Audubon's and myrtle warblers (Setophaga coronata auduboni/S. c. corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 69 publications
1
40
0
1
Order By: Relevance
“…These patterns suggest that the differentiation of myrtle warblers from the other forms is a result of strong selection in a small subset of the genome over a relatively short span of time, rather than accumulation of genomewide differences during a long period of pure geographic isolation. Admixture mapping in the hybrid zone has indicated that some of these differentiation peaks are strongly associated with colour differences between these two taxa; for example, the differentiation peak on chromosome 20 (Figure , on the left side of that chromosome) is associated with the presence of white eye spots and lines in myrtle warblers and their absence in Audubon's warblers (Brelsford, Toews, & Irwin, ).…”
Section: Discussionmentioning
confidence: 99%
“…These patterns suggest that the differentiation of myrtle warblers from the other forms is a result of strong selection in a small subset of the genome over a relatively short span of time, rather than accumulation of genomewide differences during a long period of pure geographic isolation. Admixture mapping in the hybrid zone has indicated that some of these differentiation peaks are strongly associated with colour differences between these two taxa; for example, the differentiation peak on chromosome 20 (Figure , on the left side of that chromosome) is associated with the presence of white eye spots and lines in myrtle warblers and their absence in Audubon's warblers (Brelsford, Toews, & Irwin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, approaches such as GWAS focus specifically on the variants underlying phenotypes of interest, but provide no information concerning the adaptive significance of these variants. We attempted to confront and ameliorate the limitations of these two approaches by integrating them; an idea that has only recently begun to gain traction [53,[56][57][58][59]. Our approach is unique in that we leverage LD generated by natural admixture between populations to identify genotype-phenotype associations (see also Brelsford et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to confront and ameliorate the limitations of these two approaches by integrating them; an idea that has only recently begun to gain traction [53,[56][57][58][59]. Our approach is unique in that we leverage LD generated by natural admixture between populations to identify genotype-phenotype associations (see also Brelsford et al, 2017). We first located potential adaptive regions of the genome using scans for selection then used GWAS to reveal genomic regions that are associated with multiple potentially adaptive phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The use of both metrics simultaneously ensured that the relationships observed are method agnostic. This multi-metric approach, including a combination of association and F ST outliers, has been utilized repeatedly to identify genomic regions associated with domestication in both dogs and cats (Axelsson et al 2013; Montague et al 2014), variation in feather coloration in warblers (Brelsford et al 2017), and the architecture and modularity of wing pattern variation in Heliconius butterflies (Nadeau et al 2014; Van Belleghem et al 2017). The relationship between the two metrics was explored by plotting both a correlation and a quantile-quantile plot (Q-Q plot) of the F ST and association for all variants (Fig.…”
Section: Methodsmentioning
confidence: 99%